In Focus/Diversity-An Action Plan for Developing Women Leaders - Valerio, Anna; Valerio, Anna (Center for Creative Leadership, 2006)
With the Baby Boom generation about to begin retiring and the smaller Generation X in line to provide replacements, a pressing task for many organizations is to ensure a supply of executive talent that will be ready to step into leadership roles when called upon.